Childhood acute lymphoblastic leukemia in the Middle East and neighboring countries: A prospective multi‐institutional international collaborative study (CALLME1) by the Middle East Childhood Cancer Alliance (MECCA). Issue 8 (20th March 2014) - Al‐Mulla, Naima A.; Chandra, Prem; Khattab, Mohammed; Madanat, Faris; Vossough, Parvaneh; Torfa, Eyad; Al‐Lamki, Zakiya; Zain, Gamal; Muwakkit, Samar; Mahmoud, Salah; Al‐Jassmi, Abdulrahman; Tuncer, Murat; et al.
Abstract Background Little is known about childhood ALL in the Middle East. This study was undertaken by MECCA as initial efforts in collaborative data collection to provide clinical and demographic information on children with ALL in the Middle East. Procedure Clinical and laboratory data for patients with ALL between January 2008 and April 2012 were prospectively collected from institutions in 14 Middle East countries and entered into a custom‐built‐database during induction phase. All laboratory studies including cytogenetics were done at local institutions. Results The 1, 171 voluntarily enrolled patients had a mean age of 6.1 ± 3.9 years and 59.2% were boys. T‐ALL represented 14.8% and 84.2% had B‐precursor ALL. At diagnosis, 5.6% had CNS disease. The distribution of common genetic abnormalities reflected a similar percentage of hyperdiploidy (25.6%), but a lower percentage of ETV6–RUNX1 translocation (14.7%) compared to large series reported from Western populations. By clinical criteria, 47.1% were low/standard risk, 16.9% were intermediate risk, and 36% were high risk. Most patients received all their care at the same unit (96.9%). Patients had excellent induction response to chemotherapy with an overall complete remission rate of 96%. Induction toxicities were acceptable. Conclusions This first collaborative study has established a process for prospective data collection and future multinational collaborative research in the Middle East. Despite the limitations of an incomplete population‐based study, it provides the first comprehensive baseline data on clinical characteristics, laboratory evaluation, induction outcome, and toxicity. Further work is planned to uncover possible biologic differences of ALL in the region and to improve diagnosis and management. Pediatr Blood Cancer 2014; 61:1403–1410. © 2014 Wiley Periodicals, Inc.